An analysis of the situation of children in Dien Bien 2010 : (UNICEF Vietnam, 2010)
The Analysis of the Situation of Children in Dien Bien Province provides a holistic picture of the situation of girls and boys, including an in-depth analysis of remaining challenges that children face. It also examines the possible causes of the situation of children, and analyses the province in the context of the North West region and Viet Nam as a whole. The report aims to contribute towards establishing a stronger knowledge base on children by compiling and analysing information and data on children’s issues that exists but has not yet been consolidated or comprehensively analysed.